Adaptor Protein CD2AP and L-type Lectin LMAN2 Regulate Exosome Cargo Protein Trafficking through the Golgi Complex - Kwon, Sang-Ho (J Biol Chem, 2016)
Exosomes, 40–150-nm extracellular vesicles, transport biological macromolecules that mediate intercellular communications. Although exosomes are known to originate from maturation of endosomes into multivesicular endosomes (also known as multivesicular bodies) with subsequent fusion of the multivesicular endosomes with the plasma membrane, it remains unclear how cargos are selected for exosomal release. Using an inducible expression system for the exosome cargo protein GPRC5B and following its trafficking trajectory, we show here that newly synthesized GPRC5B protein accumulates in the Golgi complex prior to its release into exosomes. The L-type lectin LMAN2 (also known as VIP36) appears to be specifically required for the accumulation of GPRC5B in the Golgi complex and restriction of GPRC5B transport along the exosomal pathway. This may occur due to interference with the adaptor protein GGA1-mediated trans Golgi network-to-endosome transport of GPRC5B. The adaptor protein CD2AP-mediated internalization following cell surface delivery appears to contribute to the Golgi accumulation of GPRC5B, possibly in parallel with biosynthetic/secretory trafficking from the endoplasmic reticulum. Our data thus reveal a Golgi-traversing pathway for exosomal release of the cargo protein GPRC5B in which CD2AP facilitates the entry and LMAN2 impedes the exit of the flux, respectively.